The Effect of Foot Soak Therapy with AGS (Warm Water, Salt, and Lemongrass) on Blood Pressure Reduction in Hypertensive Residents in Anjir Serapat Muara Village - Warda, Warda; Milasari, Milasari; Hidayati, Hidayati; Sarwani, Sarwani; Anggraini, Tri W; Rahmah, Maulida (OMNICODE Journal (Omnicompetence Community Developement Journal), 2025)
Hypertension is a major risk factor for cardiovascular diseases such as stroke and heart failure. Non-pharmacological interventions are increasingly recognized as essential alternatives, particularly due to the potential long-term side effects associated with antihypertensive medications. This study aims to examine the effect of foot soak therapy utilizing warm water, salt, and lemongrass on blood pressure reduction among individuals with hypertension. The study was conducted on 25 hypertensive residents of Anjir Serapat Muara Village. A quasi-experimental approach employing a one-group pretest-posttest design was implemented. The findings revealed that 92% of participants experienced a decrease in blood pressure following the therapy. This foot soak therapy demonstrates potential as a complementary intervention in the management of hypertension within community settings and has been proven effective in lowering blood pressure in the majority of participants.